2016
DOI: 10.4172/2157-7471.1000328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-conventional Chemicals and Synthetic Fungicide on Biochemical Characteristics of Chilli against Fruit Rot Pathogen Colletotrichum capsici

Abstract: to evaluate the effect of non-conventional chemical viz., salicylic acid, zinc sulphate, magnesium sulphate, indole acetic acid, indole butyric acid and fungicide viz., carbendazim, on total phenol, flavonol, tannin and electrolyte leakage of red fruits of chilli varieties (susceptible-Pusa Jwala and resistant-Sadabahar) against Colletotrichum capsici the causal agent of fruit rot in chilli. The phenol content was increased significantly in both the varieties (resistant and susceptible) when sprayed with salic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Yadav et al (2015) [15] found maximum induction of total phenol content in salicylic acid treated Indian mustard on five days after challenge inoculation of Alternaria blight pathogen. Geat et al (2016) [5] evaluated salicylic acid, indole acetic acid, indole butyric acid and carbendazim at 5 mM concentration against Colletotrichum capsici found more accumulation of total phenol in resistant chilli variety Sadabahar than susceptible Pusa jwala, after 48 hours of challenge inoculation of pathogen. Sugars act as precursor for synthesis of phenolics, phytoalexin, lignin, and cellulose which play an important role in defence mechanism of plant against invading pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Yadav et al (2015) [15] found maximum induction of total phenol content in salicylic acid treated Indian mustard on five days after challenge inoculation of Alternaria blight pathogen. Geat et al (2016) [5] evaluated salicylic acid, indole acetic acid, indole butyric acid and carbendazim at 5 mM concentration against Colletotrichum capsici found more accumulation of total phenol in resistant chilli variety Sadabahar than susceptible Pusa jwala, after 48 hours of challenge inoculation of pathogen. Sugars act as precursor for synthesis of phenolics, phytoalexin, lignin, and cellulose which play an important role in defence mechanism of plant against invading pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of non-conventional chemical viz., salicylic acid, zinc sulphate, magnesium sulphate, indole acetic acid, indole butyric acid with fungicide (Carbendazim). Results revealed that, increase in total phenol, flavonol, tannin and electrolyte leakage of red fruits of chilli varieties against Colletotrichumcapsici, the causal agent of fruit rot of chilli (Geat, 2016).…”
Section: S313mentioning
confidence: 95%
“…According to Ghanbary et al [70], Q. libani and Q. infectoria seedlings exposed to a combination of charcoal disease pathogens and drought showed the highest rise in EL. The first observable symptoms of pathogen infestation that cause disease are changes in membrane permeability and integrity [98]. Also, Naveed et al [20] stated that B. phytofirmans besides Enterobacter sp.…”
Section: Effect Of B Amyloliquefaciens Rash1 On El and Msi In A Alter...mentioning
confidence: 99%